A new algorithm for GMTI tracking problems, subject to a Doppler blind zone constraint - Clark, J.M.C; Kountouriotis, P.A; Vinter, R.B (IET Seminar on Target Tracking and Data Fusion: Algorithms and Applications, 2008)
This paper introduces a new methodology to take account of the Doppler blind zone arising, for example, in GMTI tracking. Here, the measurements are suppressed, when the range-rate of the target drops below a specified threshold. Algorithms based on the new methodology are easy to implement, robust to choice of initial distributions and computationally efficient. Simulations have been conducted for a number of scenarios featuring in earlier comparative exercises. The new techniques exhibit a uniform improvement in estimation accuracy, as compared with earlier proposed approximate analytic techniques.